Clinical Study of Modified Devine’s Surgical Technique in the Treatment of Concealed Penis - Zhang, Ziyi; Wu, Hao; Mao, Weijiang; Gao, Sheng-Lin; Zuo, Li; Zhang, Li-Feng (Urology Journal, 2023)
Purpose: This study aimed to observe the clinical effect of modified Devine’s surgical technique in the treatment of concealed penis. Materials and Methods: From July 2015 to September 2020, fifty-six children with concealed penis were treated with modified Devine’s technique. Recorded the penile length and the satisfaction score preoperatively and postoperatively to confirm the effect of the surgery. Followed up the penis for bleeding, infection and edema one week and four weeks after the operation. Twelve weeks after the operation, we measured the length of the penis and observed whether there was a retraction. Results: The length of the penis has been effectively lengthened(P < 0.001). There was significant improvement in parents’ satisfaction grades (P < 0.001). All the patients had different degrees of penile edema after the operation. Most of the penile edema subsided about four weeks after the operation. No other complications occurred. No obvious penile retraction was found twelve weeks postoperative. Conclusion: The modified Devine’s technique was safe and effective. As a treatment for concealed penis, it is worthy of wide clinical application.